Makna Emic Simbol-simbol Perkawinan Adat Dayak Beuaq Kenohan dan Perkawinan Katolik - Hiasintus Habibie; Martinus Nanang (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2017)
This study aims to describe the Kenohan Benuaq Dayak customary wedding rituals and compare them with the Catholic Church wedding from the aspects of the use of symbols, values and meanings embedded in the symbols. The research was done in the village of Tanjung Jan, the Sub-district of Tanjung Isuy, Kutai Barat, using qualitative method. The research found out the kinds of symbols used in the customary wedding rituals, their emic meanings and searched the similarities with the ones used in the Catholic Church wedding. Fundamentally, in marriage, the Kenohan Benuaq respect the same values as respected by the Catholic Church: love and fidelity.